Estimation of life expectancies and loss-of-life expectancies for workers with permanent occupational disabilities of the extremities - a 21-year follow-up study - Sheng-Hsuan Lin; Hsin-Yi Lee; Yu-Yin Chang; Yuh Jang; Jung-Der Wang (Nordic Association of Occupational Safety and Health (NOROSH), 2012)
OBJECTIVES: This study aims to estimate the life expectancies and loss-of-life expectancies of workers with permanent occupational disabilities of the upper and lower limbs in Taiwan. METHODS: We collected all cases of permanent occupational disability in the upper and lower limbs from the Bureau of Labor Insurance database of compensation claims between 1986-2006; these data were linked with the national mortality registry to obtain a survival function. Workers were divided into eight groups according to their injury types, three of which fulfilled the condition of constant excess hazard and the survival functions were extrapolated to 50 years using a semi-parametric method. RESULTS: Of the subjects involved in the study, 1016 with toe amputations, 995 with foot or leg amputations, and 4339 with foot or leg non-amputations showed a life expectancy of 1.8 [95% confidence interval (95% CI) -1.3- -4.9], 4.9 (95% CI 2.2- -7.6), and 4.5 (95% CI 2.1- -6.9) years, respectively. The above method was validated by extrapolating partial cohorts based on the first 10 years of follow-up data to 21-year and comparing actual survival rates using the Kaplan Meier method. The relative bias of three groups was